(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to find out the effect of career planning and career development on employees’ career commitment at the Office for Women’s Empowerment, Child Protection, and Family Planning (DP3AP2KB) in Ambalawi District, Bima Regency. The research method used is a quantitative approach with associative research type. The research instrument used in this study is a questionnaire with a Likert scale. Data is collected through questionnaires, observation, and literature review. The population consisted of 37 employees, while the sample included 34 respondents selected using a purposive sampling technique. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, multiple correlation coefficient analysis, coefficient of determination analysis, t-test (partial), and F-test (simultaneous) using SPSS version 25. The results showed that career planning has a significant effect on employees’ career commitment at the Office of Women’s Empowerment, Child Protection, and Family Planning (DP3AP2KB) in Ambalawi District, Bima Regency, with a t-value of 5.943 greater than the t-table value of 2.039 and a significance level of 0.000 < 0.05. Career development also has a significant effect on career commitment, with a t-value of 6.300 greater than the t-table value of 2.039 and a significance level of 0.000 < 0.05. Furthermore, career planning and career development simultaneously have a significant effect on employees’ career commitment, with an F-value of 75.905 greater than the F-table value of 3.29 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) value of 0.830 indicates that career planning and career development explain 83% of the variation in career commitment, while the remaining 17% is influenced by other factors not examined in this study.